2017
DOI: 10.1007/s10195-017-0443-1
|View full text |Cite
|
Sign up to set email alerts
|

Do ethnicity and gender influence posterior tibial slope?

Abstract: Background Ethnicity and gender can affect posterior tibial slope; however, studies on this topic have limitations and are in disagreement. The aim of the present study was to evaluate posterior tibial slope in a large group of consecutive patients, determining whether ethnicity and gender can influence its value. Secondly, to determine intra-and inter-rater reliability of the two radiographic methods adopted. Materials and methods Posterior tibial slope was calculated (rater 1) in lateral view X-rays of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…28 Another limitation of the study was that matching patients by ethnicity was not possible, owing to the retrospective nature of the study design, although previous studies reported race-based differences in native tibial slope. 3,29…”
Section: Discussionmentioning
confidence: 99%
“…28 Another limitation of the study was that matching patients by ethnicity was not possible, owing to the retrospective nature of the study design, although previous studies reported race-based differences in native tibial slope. 3,29…”
Section: Discussionmentioning
confidence: 99%
“…[1] Bisicchia et al measured PTS using lateral X-Ray and deemed that Asian population had PTS of 7.7°, which was larger than 6.4° of Caucasian population. [10] In our study, mean PTS of Northeast Chinese male was 8.64 ± 2.72° (Range: 4.41∼14.15°) and 9.36 ± 2.75° (Range: 4.07∼13.83°) of Northeast Chinese female. Given the different methods between above studies and our study, there was reference meaning of these studies.…”
Section: Discussionmentioning
confidence: 48%
“…First, rotation of tibia could damage the measurement accuracy and lead to overestimation. [10,15,17,23] Second, owing to overlap of medial and lateral tibia plateau, merely the PTS of proximal side could be assessed. In contrast, MPTS and LPTS could be measured respectively in 3D-level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations